A New Egg Parasitoid Species (Hymenoptera: Pteromalidae) of Monochamus alternatus (Coleoptera: Cerambycidae), with Notes on Its Biology. (1st March 2014) - Yang, Zhong-Qi; Cao, Liang-Ming; Zhang, Yan-Long; Wang, Xiao-Yi; Zhan, Mao-Kui
Abstract: A new species of Callimomoides Girault 1926 (Hymenoptera: Pteromalidae), Callimomoides monochaphagae Yang, sp. n., is described from China. It is a solitary endoparasitoid of eggs of the pine sawyer, Monochamus alternatus Hope (Coleoptera: Cerambycidae), a serious pest that causes damage to pine trees native to China, particularly Pinus massoniana Lambert and Pinus tabulaeformis Carrière. Furthermore, M. alternatus is the main vector of the pine wood nematode, Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle in China and other eastern Asian countries. C. monochaphagae has great potential as a biocontrol agent for suppression of the longhorned beetle because parasitism rates of 12.6% have been observed and this species has a relative high female:male sex ratio (1.86:1). Detailed photographs of the key characters of the new species are supplied. In addition, a key to the currently known species of Callimomoides throughout the world is provided. Type specimens are deposited in the Insect Museum, Chinese Academy of Forestry, Beijing, China.